Postfire nitrogen balance of Mediterranean shrublands: Direct combustion losses versus gaseous and leaching losses from the postfire soil mineral nitrogen flush - Dannenmann, Michael; Díaz Pinés, Eugenio; Kitzler, B.; Karhu, K.; Tejedor, J.; Ambus, P.; Parra, A.; Sánchez Martin, L.; Resco, V.; Ramírez, D.; Povoas-Guimaraes, L.; Willibald, G.; et al. (Wiley, 2018)
Fire is a major factor controlling global carbon (C) and nitrogen (N) cycling. While direct C and N losses caused by combustion have been comparably well established, important knowledge gaps remain on postfire N losses. Here, we quantified both direct C and N combustion losses as well as postfire gaseous losses (N2O, NO and N2) and N leaching after a high‐intensity experimental fire in an old shrubland in central Spain. Combustion losses of C and N were 9.4 Mg C/ha and 129 kg N/ha, respectively, representing 66% and 58% of initial aboveground vegetation and litter stocks. Moreover, fire strongly increased soil mineral N concentrations by several magnitudes to a maximum of 44 kg N/ha 2 months after the fire, with N largely originating from dead soil microbes. Postfire soil emissions increased from 5.4 to 10.1 kg N ha−1 year−1 for N2, from 1.1 to 1.9 kg N ha−1 year−1 for NO and from 0.05 to 0.2 kg N ha−1 year−1 for N2O. Maximal leaching losses occurred 2 months after peak soil mineral N concentrations, but remained with 0.1 kg N ha−1 year−1 of minor importance for the postfire N mass balance. 15N stable isotope labelling revealed that 33% of the mineral N produced by fire was incorporated in stable soil N pools, while the remainder was lost. Overall, our work reveals significant postfire N losses dominated by emissions of N2 that need to be considered when assessing fire effects on ecosystem N cycling and mass balance. We propose indirect N gas emissions factors for the first postfire year, equalling to 7.7% (N2‐N), 2.7% (NO‐N) and 5.0% (N2O‐N) of the direct fire combustion losses of the respective N gas species.